2022
DOI: 10.3390/vaccines10060832
|View full text |Cite
|
Sign up to set email alerts
|

Acceptance of and Preference for COVID-19 Vaccination in India, the United Kingdom, Germany, Italy, and Spain: An International Cross-Sectional Study

Abstract: Objective: India and Europe have large populations, a large number of Coronavirus disease 2019 (COVID-19) cases, and different healthcare systems. This study aims to investigate the differences between the hesitancy toward and preference for COVID-19 vaccines in India and four European countries, namely, the United Kingdom (UK), Germany, Italy, and Spain. Methodology: We conducted a cross-national survey for distribution in India, the UK, Germany, Italy, and Spain. More specifically, a discrete choice experime… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 49 publications
0
9
0
Order By: Relevance
“…A review paper showed that the prevalence of hesitancy for COVID-19 vaccination varied from 4.3% to 72% among healthcare workers worldwide [ 41 ]. Possible explanations for the disparities might include policy and socio-cultural differences and different time points [ 39 , 42 , 43 ]. Due to the issues of methodology (for example, imbalanced response options) and self-selection of respondents, the prevalence of refusal is likely to be overestimated.…”
Section: Discussionmentioning
confidence: 99%
“…A review paper showed that the prevalence of hesitancy for COVID-19 vaccination varied from 4.3% to 72% among healthcare workers worldwide [ 41 ]. Possible explanations for the disparities might include policy and socio-cultural differences and different time points [ 39 , 42 , 43 ]. Due to the issues of methodology (for example, imbalanced response options) and self-selection of respondents, the prevalence of refusal is likely to be overestimated.…”
Section: Discussionmentioning
confidence: 99%
“…The number of COVID-19 cases began to rise rapidly around mid-April. As of August 7, 2022, Russia was ranked ninth in the world in terms of the number of COVID-19 instances, behind the United Kingdom and Italy ( 84 , 85 ). COVID-19 cases totaled 18,485,632 in Russia, with 381,835 deaths, despite an ongoing battle against the disease's rapid spread ( 78 ).…”
Section: Results Designmentioning
confidence: 99%
“…Processes 2022, 10, 1665 2 of 19 deaths [3]. For example, the statistics from a study conducted in India revealed the severe consequences of COVID-19 on the country in terms of affecting India's economy and causing social unrest and increased rates of domestic violence [2].…”
Section: Introductionmentioning
confidence: 99%
“…Since neighboring countries have influenced each other in battling COVID-19, the countries are generally listed below according to their geographic locations. Studies in four European countries (i.e., the UK, Germany, Italy, and Spain) and India found that the vaccine efficacy followed by the vaccine cost were considered the most prominent factors in vaccine hesitancy [3], while studies in France found a direct correlation between knowledge of the vaccine's safety and vaccination rates [7]. Meanwhile, the studies conducted by Toshkov 2022 [9] using the data from Eurobarometer for 27 European Union countries determined that individuals who trust the Internet and social networks as sources of information on health were less likely to trust the COVID-19 vaccine.…”
Section: Introductionmentioning
confidence: 99%